Efektifitas Layanan Call Center 110 Polda Bali Dalam Penanganan Kecelakaan Lalu Lintas Di Kota Denpasar - I Gede Permana Adithya; Agustina Ni Made Ayu Darma Pratiwi (Jurnal Hukum Mahasiswa, 2026)
The National Police Call center 110 service is one of the police’s public service mechanisms that allows the community to report issues related to public security disturbances or criminal/violation incidents via the telephone number 110. However, in practice, the Call center 110 service has not been fully effective in handling traffic accidents in Denpasar City. Therefore, the researcher formulates the research problems as follows: how effective is the Bali Regional Police Call center 110 service in handling traffic accidents in Denpasar City, and what are the inhibiting factors in handling traffic accidents in Denpasar City through the Call center 110 service of the Bali Regional Police. The research method used in this thesis is empirical legal research or field research. The conclusion of this study indicates that the Call center 110 service of the Bali Regional Police has not been effective in handling traffic accidents in Denpasar City. This is due to inhibiting factors originating from both internal and externalaspects